Influence of co‐morbidity on long‐term quality of life after oesophagectomy for cancer. Issue 5 (29th January 2014) - Djärv, T.; Derogar, M.; Lagergren, P.
<x xml:space="preserve">Abstract</x> Background The extent to which co‐morbidities affect recovery of health‐related quality of life (HRQoL) in long‐term survivors of oesophageal cancer surgery is poorly understood. Methods This was a prospective, population‐based, nationwide Swedish cohort study of patients who underwent surgery for oesophageal cancer between 2001 and 2005, and were alive 5 years after operation. The European Organization for Research and Treatment of Cancer QLQ‐C30 and the QLQ‐OES18 questionnaires were used to assess HRQoL up to 5 years after surgery. Eight aspects from the questionnaires were selected. Matched reference values from the Swedish general population were used as a proxy for HRQoL before presentation of the cancer. Adjusted multivariable linear mixed‐effect models were used to assess mean score differences (MDs) of each HRQoL aspect in patients with or without co‐morbidities. Results Of 616 patients who underwent surgery, 153 (24·8 per cent) survived 5 years, of whom 141 (92·2 per cent) completed the questionnaires at 5 years. Among these, 79 (56·0 per cent) had co‐morbidities. Patients with co‐morbidity had clinically relevant (MD at least 10) and statistically significantly poorer global quality of life (MD −10, 95 per cent confidence interval −12 to −7), and more problems with dyspnoea (MD 10, 6 to 13) throughout the whole follow‐up period than those without co‐morbidity. Patients with co‐morbidity had a clinically relevant worse level of fatigue at 6 months (MD 10, 1 to 19) and 5 years (14, 4 to 24). With regard to specific co‐morbidities, only patients with diabetes reported more clinically relevant, but not statistically significant, problems with fatigue at 6 months (MD 16, 2 to 31) and 5 years (MD 13, –5 to 31) compared with patients without co‐morbidity. Conclusion Among survivors of oesophageal cancer surgery, the presence of co‐morbidity was associated with poor HRQoL over time and increasing symptoms of fatigue.